2013
DOI: 10.1111/resp.12028
|View full text |Cite
|
Sign up to set email alerts
|

Triggering receptor expressed on myeloid cells‐1 and 2 in bronchoalveolar lavage fluid in pulmonary sarcoidosis

Abstract: Background and objective: Pulmonary sarcoidosis (PS) is characterized by the formation of granulomas in the lungs and has been associated with infection by microorganisms. Triggering receptor expressed on the surface of myeloid cells (TREM)-1 is overexpressed in response to infection while TREM-2 is involved in granuloma formation. We hypothesized that these receptors are overexpressed in PS and might be useful for diagnostic testing. Methods: Cell surface TREM-1 and TREM-2 expression in cells obtained at bron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…CD8 ratio test together with TREM-1 and TREM-2 test resulted in an increased sensitivity and specifi city. Signifi cant association of increased TREM-1 and TREM-2 expression on myeloid cell surfaces in BALF of PS patients has been detected also in our previous study (19). According to these two studies, we might conclude, that increase in both of these receptors are typical for PS diagnosis and can represent a new diagnostic marker for PS.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…CD8 ratio test together with TREM-1 and TREM-2 test resulted in an increased sensitivity and specifi city. Signifi cant association of increased TREM-1 and TREM-2 expression on myeloid cell surfaces in BALF of PS patients has been detected also in our previous study (19). According to these two studies, we might conclude, that increase in both of these receptors are typical for PS diagnosis and can represent a new diagnostic marker for PS.…”
Section: Discussionmentioning
confidence: 60%
“…TREM-1 and TREM-2 receptor expressions appear to be a good diagnostic marker with a relatively high sensitivity and specifi city (19).…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Suchankova et al . undertook a study of myeloid cells isolated from the bronchoalveolar lavage of patients with sarcoid . They explored the expression pattern of triggering receptor expressed on myeloid cells‐1 and ‐2.…”
Section: Interstitial Lung Diseasesmentioning
confidence: 99%
“…So, these receptors reflect two typical signs of sarcoidosis: (1), inflammation and antimicrobial response (through TREM-1) and (2) phagocytosis and multinucleated cells and granuloma formation (through TREM-2 and DAP-12 signalling). In our previous study we showed an increased expression of both TREM-1 and TREM-2 receptors on the surface of myeloid cells in bronchoalveolar lavage fluid (BALF) in pulmonary sarcoidosis (PS) and increased levels of soluble sTREM-1 in BALF of PS patients [ 18 , 19 ]. There are a few studies concerning the levels of vitamin D and TREM receptor expressions.…”
Section: Introductionmentioning
confidence: 99%